TRENDS IN ATTRACTION AND SPATIAL DISTRIBUTION OF TRANSNATIONAL CORPORATION INVESTMENT FLOWS IN THE DIGITAL ERA - Кірієнко, Сергій (SWorldJournal, 2025)
This article investigates current trends in the attraction and spatial distribution of Transnational Corporations’ (TNCs)investment flows in the context of the global digital economy. The study’s relevance is driven by the fundamental transformation of TN